Effectiveness of participatory training in preventing accidental occupational injuries: a randomized-controlled trial in China - Ignatius TS Yu; Wenzhou Yu; Zhimin Li; Hong Qiu; Sabrina Wan; Shaohua Xie; Xiaorong Wang (Nordic Association of Occupational Safety and Health (NOROSH), 2017)
OBJECTIVE: The aim of this study was to evaluate the effectiveness of a participatory training program in preventing accidental occupational injuries in factories in Shenzhen, China. METHODS: We conducted a cluster randomized study with the worker as the unit of analysis, providing 918 workers from 30 factories participatory training. Two control groups received traditional didactic training, including 907 workers from the same 30 factories and 1654 workers in matched control factories. We used generalized estimating equations to compare the before/after person-based injury rate difference in the three groups and binary logistic regression to compare the re-injury rates. RESULTS: The person- and event-based incidence rates of accidental injury in the intervention group reduced from 89.3 to 52.1 per 1000 workers (P=0.002) and from 138.3 to 74.5 per 1000 person-years (P<0.001), respectively. The rate reductions in the two control groups were not statistically significant. Compared with the intervention group, the risk of accidental work injury over time was higher in the control groups, with odds ratios (OR) 1.78 (1.04-3.04) and 1.77 (1.13-2.79) for control_1 and control_2 group, respectively. The re-injury rates were 27.1% (13/48) in the intervention group, and 41.7% (15/36) and 52.6% (51/97) in the two control groups respectively, with the latter being significantly higher than the intervention group. CONCLUSIONS: Our study documented the effectiveness of a participatory approach to occupational health and safety training in reducing accidental work injuries and re-injuries among frontline workers.